(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s
(3ChdgG (B:s
(3fhGRd GdhcGdGJ hSFd GdCSJGP CHh SYjO aQL Hf GdbGSe Hf dH Yf Gdhcjd jYLR Yf EMVGQ ehcdg , aCLGH s
(3BNQgG (B:s
(3hGYde Cfg jdRe ef bhdg Cfg djS ef GdCgd hdG ef GdbQGHI eG CdRefGg ef chfg Yf GdPQjI adG aGFOI ef GdJcQGQ , hCeG eG LGhH Hg ZjQg aJQc GdLhGH hGdJYQV dg gh GdLhGH , hGddg Gdehab bGd GdeDda bO EfJgjJ ef gPg GdCLhHI s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdCShO hHGdCMeQ GdSejcs
(3Ydi WQJgG Jedc HGSe GdabjQ EHQGgje Hh NQjSI s
(3HgG fhGRd GdhcGdGJ hGdEbQGQGJ hGdeOjGf hGdLGeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs